Nowoczesny szpital - efektywność inwestycji, wymagania rynkowe - Słabiak, Artur (Modern Hospital, Investment Efficiency, Market Demands, 2006)
The author presents his personal experiences obtained during his work for Health Care Units in West Europe and Poland. Contemporary trends in designing hospitals in West Europe do not focus on enlargement, but on effective use of space, staff and equipment and on lowering exploitation costs. The main functions of such units are presently organized around certain complementary areas. At the same time basic market needs are being fulfilled. Unfortunately, Poles still follow the rule "the more complete and the bigger a hospital the more modern it is" and rational needs assessment is displaced by regulations and customs which are very difficult to implement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 135-143